What helps and hinders reproducible research? Researchers’ perspectives from a cross-disciplinary interview study - Magdalena Kozula; Nicholas J. DeVito; Patrick Onghena; Cinzia Colombo; Leonie A. Dudda; Paula Muñoz Teno; Veerle Van den Eynden (PLoS ONE, 2026)
Debates and policy initiatives addressing research reproducibility have expanded considerably in recent years. Yet, many of these measures remain generic and risk overlooking the lived realities of research practice. This study aims to explore researchers’ perspectives on the barriers, facilitators, and motivators that shape reproducible research across diverse fields and career stages, using qualitative methods. Semi-structured interviews were conducted with 60 researchers affiliated with universities and research institutions across the European Union and the United Kingdom. Participants were sampled to ensure diversity in discipline, career stage, gender, and geography. The interviews explored experiences with barriers and facilitators for reproducible research, and the data were analyzed using framework analysis with a hybrid inductive–deductive approach. Five interrelated themes described barriers and facilitators influencing reproducibility: navigating the research ecosystem (incentives and policies of institutions, journals, and funders); social and cultural dynamics as drivers and barriers (disciplinary norms, generational differences, competition, and collaboration); resourcing reproducibility (skills, infrastructure, guidelines and standards, time, funding, and awareness); inside the research process (field-specific constraints, methodological transparency, research material sharing, and external restrictions); and personal commitment to shared responsibility (reflective motivations, pragmatic drivers, and perceptions of accountability). Researchers described reproducibility as less of an individual choice but as a socially and institutionally mediated activity, dependent on enabling conditions such as supportive policies, adequate infrastructure, and equitable resource distribution. Reproducibility reform cannot rely solely on individual researcher commitment or one-size-fits-all policies. Effective interventions must account for disciplinary and methodological diversity, provide targeted resources and training, and realign incentive structures to reward transparency and rigour. These findings highlight reproducibility as a collective responsibility across the research ecosystem, requiring coordinated action by researchers, institutions, funders, and publishers. Promoting reproducible practices in this systemic, context-sensitive manner is essential for fostering a more credible, equitable, and sustainable scientific enterprise.